Pain Assessment in Patellar Tendinopathy Using Pain Pressure Threshold Algometry: An Observational Study. Issue 11 (26th June 2013) - Kregel, Jeroen; van, Cornelis Paul; Zwerver, Johannes
Abstract Objective Assessing pain in patellar tendinopathy (PT) is difficult to perform in a standardized way. With this study, we measured pain in athletes with PT by means of pain pressure threshold (PPT) algometry in a standardized manner. Subsequently, the goal of this study is to determine normative values for clinical use. Design Observational study. Setting Patients and healthy subjects were recruited from an outpatient clinic of a university medical center and at different sports clubs in northern Netherlands. Subjects A total of 234 athletes, 114 diagnosed with PT and 120 healthy controls, were included. Outcome Measures PPT, Victorian Institute of Sport Assessment—Patellar tendinopathy questionnaire, and visual analog scale–pain. Results PPT scores of PT athletes with tendinopathy were significantly lower compared with healthy athletes (Mann–Whitney U‐test; U = 293.5; P < 0.001). With a receiver operating characteristic (ROC) curve, the optimal cut‐off point to distinguish between healthy athletes and PT athletes was calculated at 36.8 N. The area under the ROC curve was 0.98 (95% CI: 0.96–1.0). There was a positive predictive value of 96.5% that athletes with a PPT below 36.8 N. had PT. Conclusions PPT algometry should be considered by clinicians as a pain assessment tool in patients with PT. The optimal cut‐off point for the PPT to distinguish between PT athletes and healthy athletes was 36.8 N.